Development and Validation of a Novel ELISA for the Specific Detection of Antibodies against Mycobacterium avium Subspecies paratuberculosis Based on a Chimeric Polyprotein - Roberto Damián Moyano; Magali Andrea Romero; María Alejandra Colombatti Olivieri; María Fiorella Alvarado Pinedo; Gabriel Eduardo Traveria; María Isabel Romano; María Natalia Alonso (Veterinary Medicine International)
Bovine paratuberculosis (PTB) is caused by Mycobacterium avium subsp. paratuberculosis (MAP). The optimization of detection tests specific for MAP is crucial to improve PTB control. In this work, we aimed to develop and validate a diagnostic tool based on an ELISA to specifically detect anti-MAP antibodies from bovine serum samples. For that purpose, we designed a recombinant polyprotein containing four specific antigens from MAP and optimized the ELISA. The validation consisted of the assessment of 10 sera from PTB-infected and healthy bovines with different OD values. The diagnostic performance of the polyprotein-ELISA was evaluated by testing 130 bovine serum samples (47 healthy, 48 MAP-infected, and 35 M. bovis-infected bovines). The ELISA using the polyprotein yielded an area under the ROC curve (AUC) of 0.9912 (95% CI, 0.9758–1.007; P < 0.0001). Moreover, for this ELISA, the cut-off selected from the ROC curve based on the point with a sensitivity of 95.56% (95% CI, 0.8485–0.9946) and specificity of 97.92 (95% CI, 0.8893–0.9995) was 0.3328. Similar results were obtained with an ELISA using the commercial Paratuberculosis Protoplasmatic Antigen (PPA). However, the ELISA with the polyprotein antigen showed a better performance against sera from animals infected with Mycobacterium bovis compared to the ELISA with PPA: lower cross-reactivity (2.85% versus 25.71%). These results demonstrate a very low cross-reactivity of the polyprotein with antibodies present in serum samples from animals infected with M. bovis. The designed polyprotein and the validated ELISA could be very useful for the specific identification of MAP-infected animals in herds.